Analisis Buku Ajar Bahasa Arab Berdasarkan Prinsip (Studi Analisis Buku Bahasa Arab kelas 8 pada semester 1) - Alfi Nurrosyiid; Nurselafia; Muhammad Tareh Aziz (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2022)
Books have an important role in teaching and learning activities and the development of knowledge. The MTS grade 8 Arabic textbook published by the Indonesian Ministry of Religion, which should have been thoroughly researched before being published, is alleged to contain several errors. Therefore, this analysis needs to be done to correct and evaluate errors in writing Arabic textbooks. This study uses a qualitative approach to library research or what is called library research. In this analysis the researcher uses content analysis data collection techniques or what is often called "Content Analysis". The MTS Grade 8 Arabic textbook published by the Ministry of Religion of the Republic of Indonesia includes core competencies, basic competencies and indicators but does not include graduation standards. The learning material contains 3 themes, الساعة، يومياتنا، الهواية. The textbook material for learning Arabic for class 8 MTS is relevant to basic competencies but still has some deficiencies. This textbook material for learning Arabic for class 8 MTS published by the Ministry of Religion is consistent with basic competencies. However, there are some deficiencies in its preparation, namely the material for the nahwu rules in each chapter. In the principle of adequacy, it is felt that this is not enough, because for learning Arabic students must have the ability of four maharahs, but in the book there are no clear instructions for having conversations with friends.